Introduction to the thematic collection - Ola Leifler; Cecilia Enberg (Högre Utbildning, 2020)
In the current thematic collection of Högre Utbildning, we present eight contributions on how to change higher education in ways which will enable students to contribute to a sustainable future, including three invited papers on the systematic transformation of higher education necessary to address our existential societal challenges.